Does Affirmative Action Work? Caste, Gender, College Quality, and Academic Success in India - Bagde, Surendrakumar; Epple, Dennis; Taylor, Lowell (American Economic Review, 2016)
Public policy in modern India features affirmative action programs intended to reduce inequality that stems from a centuries-old caste structure and history of disparate treatment by gender. We study the effects of one such affirmative action program: an admissions policy that fixes percentage quotas, common across more than 200 engineering colleges, for disadvantaged castes and for women. We show that the program increases college attendance of targeted students, particularly at relatively higher-quality institutions. An important concern is that affirmative action might harm intended beneficiaries by placing them in academic programs for which they are ill-prepared. We find no evidence of such adverse impacts. (JEL O15, O17, I23, I28, J15, J16, Z13)